Gravimetric determination of Cd (II) by guanidilthioureia - Capitán, F.; Canales, F. (Ars Pharmaceutica (Internet), 1965)
In this work we propose a method for the gravimetric determination of Cd (II) based on the use of guanidyl thiourea and consistent, in essence, in transforming the SCd obtained in the SO4Cd by the action of the reactant in an ammoniacal medium. The results obtained show that the method allows a standard deviation of 0.0003 and an error on the average of +/- 0.18%.